Inhibition of Bacterial Quorum Sensing and Biofilm Formation by Extracts of Neotropical Rainforest Plants - Ta, Chieu Anh; Freundorfer, Marie; Mah, Thien-Fah; Otárola-Rojas, Marco; Garcia, Mario; Sanchez-Vindas, Pablo; Poveda, Luis; Maschek, J. Alan; Baker, Bill J.; Adonizio, Allison L.; Downum, Kelsey; Durst, Tony; Arnason, John T. (Planta Medica, 2014)
Bacterial biofilms are responsible for many persistent infections by many clinically relevant pathogens such as Staphylococcus aureus and Pseudomonas aeruginosa. Biofilms are much more resistant to conventional antibiotics than their planktonic counterparts. Quorum sensing, an intercellular communication system, controls pathogenesis and biofilm formation in most bacterial species. Quorum sensing provides an important pharmacological target since its inhibition does not provide a selective pressure for resistance. In this study, we investigated the quorum sensing and biofilm inhibitory activities of 126 plant extracts from 71 species collected from neotropical rainforests in Costa Rica. Quorum sensing and biofilm interference were assessed using a modified disc diffusion bioassay with Chromobacterium violaceum ATCC 12 472 and a spectrophotometric bioassay with Pseudomonas aeruginosa PA14, respectively. Species with significant anti-quorum sensing and/or anti-biofilm activities belonged to the Meliaceae, Melastomataceae, Lepidobotryaceae, Sapindaceae, and Simaroubaceae families. IC50 values ranged from 45 to 266 µg/mL. Extracts of these active species could lead to future development of botanical treatments for biofilm-associated infections.
Keywords: biofilms; quorum sensing; Meliaceae; Melastomataceae; Piperaceae; violacein; Chromobacterium violaceum; Pseudomonas aeruginosa